2015
DOI: 10.1007/s11524-015-9962-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the Association between Neighborhood Drug Prevalence and Marijuana use Independent of Peer Drug and Alcohol Norms? Results from a Household Survey of Urban Youth

Abstract: To inform policy debates surrounding marijuana decriminalization and add to our understanding of social and structural influences on youth drug use, we sought to determine whether there was an independent association between neighborhood drug prevalence and individual-level marijuana use after controlling for peer drug and alcohol norms. We analyzed cross-sectional data from a household survey of 563 youth aged 15-24 in Baltimore, Maryland. The study population was 88 % African-American. Using gender-stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Empirical studies have also documented possible gender differences in the association of financial and employment-related stressors with substance use (Boden et al, 2014; Mulia et al, 2014; Redonnet et al, 2012; Rospenda et al, 2008) in the impact of neighborhood factors on substance use (Fone et al, 2013; Kuipers et al, 2012; Leifheit et al, 2015; Matheson et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have also documented possible gender differences in the association of financial and employment-related stressors with substance use (Boden et al, 2014; Mulia et al, 2014; Redonnet et al, 2012; Rospenda et al, 2008) in the impact of neighborhood factors on substance use (Fone et al, 2013; Kuipers et al, 2012; Leifheit et al, 2015; Matheson et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that neighborhoods significantly encourage engagement in social activities, especially for adolescents [ 22 ]. Thus, regularly witnessing substance use and having it readily available can increase the likelihood of use, can encourage normalization of these behaviors, and can contribute to later substance use in Latino and Black adolescents [ 22 , 23 , 24 ]. Research found that high visibility of drug sales was the biggest disadvantage of densely populated neighborhoods for Black youths [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhoods are a promising point of intervention to alter substance use behaviors; mounting evidence suggests that aspects of the neighborhood environment influence risk of problematic drug use among adolescents (11–13). However, reducing exposure to neighborhood poverty has not resulted in uniformly beneficial effects on drug use and abuse among adolescents.…”
Section: Introductionmentioning
confidence: 99%